2022
DOI: 10.1002/adma.202107351
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplasmonics in Solar Energy Conversion: Materials, Nanostructured Designs, and Applications

Abstract: The indispensable requirement for sustainable development of human society has forced almost all countries to seek highly efficient and cost‐effective ways to harvest and convert solar energy. Though continuous progress has advanced, it remains a daunting challenge to achieve full‐spectrum solar absorption and maximize the conversion efficiency of sunlight. Recently, thermoplasmonics has emerged as a promising solution, which involves several beneficial effects including enhanced light absorption and scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 299 publications
(553 reference statements)
1
56
0
Order By: Relevance
“…This indicates that, due to the wide band-gap characteristics of semiconductors, their light absorption range is limited. Thus, heteroatom doping, defect engineering, morphology design, and metal loading have emerged to expand the light absorption region of catalysts. ,, Among them, metal-supported semiconductor catalysts occupy an important status in the field of catalysis. In this way, an intermediate energy state is generated for electron transition, which means that photogenerated electrons with lower energy can be excited and recombination of electron–hole pairs can be prevented (Figure b–d).…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that, due to the wide band-gap characteristics of semiconductors, their light absorption range is limited. Thus, heteroatom doping, defect engineering, morphology design, and metal loading have emerged to expand the light absorption region of catalysts. ,, Among them, metal-supported semiconductor catalysts occupy an important status in the field of catalysis. In this way, an intermediate energy state is generated for electron transition, which means that photogenerated electrons with lower energy can be excited and recombination of electron–hole pairs can be prevented (Figure b–d).…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
“…In 2014, Ye and collaborators investigated the photothermal catalytic CO 2 methanation properties of supported Group VIII metals (Ru, Rh, Ni, Co, Pd, Pt, Ir, and Fe), and the results indicated that the strong light absorption properties of the metal nanoparticles could efficiently accelerate the catalytic process due to the increased local temperatures . The research showed that the loaded metal nanoparticles on the surface of the supports usually exhibited a localized surface plasmon resonance, which could focus light in the nanoscale. , These plasmonic materials feature efficient generation and separation of photoinduced carriers when loaded on semiconducting photocatalysts and can harness the full potential of photothermal conversion with a high capacity for heat generation. There are photocatalytic and photothermal processes occurring simultaneously on the metal/semiconductor catalysts.…”
Section: Catalyst Development For Photopromoted Carbon Dioxide Methan...mentioning
confidence: 99%
“…High-performance PTMs should satisfy the following conditions: broadband sunlight absorption, hydrophilic porous structure, and excellent stability. The reported PTMs can be mainly categorized as metallic plasmonic materials, 2 semiconductor Ming Li and Zhenning Zhang are considered to be co-first authors for their equal contribution to this work. materials, 3 and carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…High‐performance PTMs should satisfy the following conditions: broadband sunlight absorption, hydrophilic porous structure, and excellent stability. The reported PTMs can be mainly categorized as metallic plasmonic materials, 2 semiconductor materials, 3 and carbon materials 4 . For instance, Zhu exploited an Au plasmonic absorber through self‐assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Highperformance PTMs generally have the following three typical characteristics: (1) full wavelength sunlight absorption for efficient photothermal efficiency; (2) excellent hydrophilic property to rapidly wet the PTMs for high Jun Xiong and Zhihui Yang contributed equally to this work and should be considered co-first authors evaporation rate; (3) outstanding chemical and thermal stability for long-term service. A major subcategory of PTMs is based on metallic plasmonic materials, 7 which have an extraordinary ability to convert sunlight into heat thanks to their strong field enhancement, low plasmon dissipation losses, and fast capillary flow. However, some metallic nanoparticles such as Au and Ag are costly, and most nanoparticles like Fe and Cu are unstable in corrosive media.…”
Section: Introductionmentioning
confidence: 99%